A New Stabilized Finite Element Method for Solving the Advection-Diffusion Equations (Journal of Computational Mathematics, 2002)
This paper is devoted to the development of a new stabilized finite element method for solving the advection-diffusion equations having the form $-κΔ u+\underline{a}\bullet\underline{ abla}u+σ u=f$ with a zero Dirichlet boundary condition. We show that this methodology is coercive and has a uniformly optimal convergence result for all mesh-Peclet number.